High-definition-iSCAN virtual chromoendoscopy has high sensitivity and specificity for the diagnosis of eosinophilic esophagitis - Gregory, Eustace; Fort Gasia, Miriam; Gui, Xianyong; Ghosh, Subrata; Iacucci, Marietta (Endoscopy International Open, 2017)
Background and study aims A major challenge in eosinophilic esophagitis (EoE) is disease recognition during endoscopy as there are no pathognomonic findings. We aimed to determine the utility of high-definition (HD) iSCAN virtual chromoendoscopy (VC) in diagnosis of EoE.Patients and methods One hundred eighty-nine consecutive patients presenting with dysphagia or food bolus impaction were assessed using HD-iSCAN VC (Pentax, Japan) with biopsies from distal, mid, upper esophagus and from furrows where visible. Results Of 189 patients, 45 (23.8 %, male = 29, median age 40y) had a histological diagnosis of EoE; 73.3 % of the patients were newly diagnosed. iSCAN endoscopic features of EoE were linear furrows (91 %), edema (77.8 %), rings or tracheal appearance (73.3 %), whitish exudates (26.6 %) and narrowing or stricture (5 %). One patient (2.2 %) had all 5 endoscopic features. Ten patients (22.2 %) had linear furrows, edema,rings or tracheal appearance and whitish exudates on iSCAN, with a positive predictive value (PPV) 100 % (95 % CI 69.1 %-100 %) and negative predictive value (NPV) 80.4 % (95 % CI 73.9 %-86 %). Thirteen patients (29 %) presented with linear furrows, edema and rings or tracheal appearance on iSCAN, with a PPV 100 % (95 % CI 75.3 %-100 %) and NPV 81.8 % (95 % CI 75.3 %-87.2 %). Six patients (13.3 %) had furrows and edema and 6 patients (13.3 %) had furrows and rings or tracheal appearance on iSCAN, with a PPV 100 % (95 % CI 54.1 %-100 %) and NPV 78.69 % (95 % CI 72 %-84.4 %), respectively. The sensitivity and specificity of HD-iSCAN endoscopy were 97.62 % (95 % CI 87.43 %-99.94 %) and 89.58 % (95 % CI 83.40 %-94.05 %). The accuracy of HD-iSCAN endoscopy was 92.47 % (95 % CI 87.67 %-95.56 %).Conclusion HD-iSCAN endoscopy is sensitive and specific with good accuracy for EoE diagnosis. Linear furrows, edema and tracheal appearance were the most common findings and these 3 endoscopic features had a high predictive value for diagnosis of EoE.